Global insights into MRSA bacteremia: a bibliometric analysis and future outlook - Lin, Jia-Yi; Lai, Jia-Kai; Chen, Jian-Yi; Cai, Jia-Yu; Yang, Zhan-Dong; Yang, Liu-Qingqing; Zheng, Ze-Tao; Guo, Xu-Guang (Frontiers in Microbiology, 2025)
BackgroundMethicillin-resistant Staphylococcus aureus (MRSA) bloodstream infections (BSIs) pose a significant challenge to global public health, characterized by high morbidity and mortality rates, particularly in immunocompromised patients. Despite extensive research, the rapid development of MRSA antibiotic resistance has outpaced current treatment methods, increasing the difficulty of treatment. Therefore, reviewing research on MRSA BSIs is crucial.MethodsThis study conducted a bibliometric analysis, retrieving and analyzing 1,621 publications related to MRSA BSIs from 2006 to 2024. The literature was sourced from the Web of Science Core Collection (WoSCC), and data visualization and trend analysis were performed using VOSviewer, CiteSpace, and Bibliometrix software packages.ResultsThe bibliometric analysis showed that research on MRSA BSIs was primarily concentrated in the United States, China, and Japan. The United States leads in research output and influence, with significant contributions from institutions such as the University of California system and the University of Texas system. The journal with the most publications is Antimicrobial Agents and Chemotherapy, while the most cited global publication is Vincent JL’s article “Sepsis in European Intensive Care Units: Results of the SOAP Study” published in Critical Care Medicine in 2006. Cosgrove SE’s article “Comparison of Mortality Associated with Methicillin-Resistant and Methicillin-Susceptible Staphylococcus aureus Bacteremia: A Meta-analysis” had the most co-citations. Key trends in the research include MRSA’s antibiotic resistance mechanisms, the application of new diagnostic technologies, and the impact of COVID-19 on MRSA studies. Additionally, artificial intelligence (AI) and machine learning are increasingly applied in MRSA diagnosis and treatment, and phage therapy and vaccine development have become future research hotspots.ConclusionMethicillin-resistant Staphylococcus aureus BSIs remain a major global public health challenge, especially with the increasing severity of antibiotic resistance. Although progress has been made in new treatments and diagnostic technologies, further validation is required. Future research will rely on integrating genomics, AI, and machine learning to drive personalized treatment. Strengthening global cooperation, particularly in resource-limited countries, will be key to effectively addressing MRSA BSIs.